2012 3rd IEEE PES Innovative Smart Grid Technologies Europe (ISGT Europe) 2012
DOI: 10.1109/isgteurope.2012.6465644
|View full text |Cite
|
Sign up to set email alerts
|

Parameter identification of unknown radial grids for theft detection

Abstract: This paper proposes an algorithm to detect the stealing of electricity by illegal connections in smart grids with unknown or uncertain cable lengths. Many new applications in the rising smart grid context will require information of the grid topology. We show that with measurement data of smart meters, the grid can be identified, as well as the phase of connection. One of the applications requiring grid information is the detection of electricity theft by double feeding. Electricity theft is a problem faced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…When Monte Carlo noise was added to real measurements, in order to produce data for baseline construction, it was concluded that the active power injection residues of the generators are impacted the most by the attack. Weckx et al in [14] propose a linearized load flow algorithmic approach using SM data for electricity theft detection via illegal connections, when line lengths are unknown or uncertain. At the same time, basic information of the topology can be extracted and the phase of consumers can be identified in an automatic way.…”
Section: System State-based Methodsmentioning
confidence: 99%
“…When Monte Carlo noise was added to real measurements, in order to produce data for baseline construction, it was concluded that the active power injection residues of the generators are impacted the most by the attack. Weckx et al in [14] propose a linearized load flow algorithmic approach using SM data for electricity theft detection via illegal connections, when line lengths are unknown or uncertain. At the same time, basic information of the topology can be extracted and the phase of consumers can be identified in an automatic way.…”
Section: System State-based Methodsmentioning
confidence: 99%
“…al [11] propose an algorithm that first finds out a fraudulent user's transformer, and then tries to identify the particular fraudulent user by analyzing the energy consumption variance of all the users connected to the transformer. Weckx et al [12] can find energy thieves by modeling a distribution network as a linear equation, only if all the voltage measurements and some initial power measurements are authentic, i.e., not tampered by the energy thieves. Unfortunately, we find that all these techniques have low detection rates.…”
Section: Related Workmentioning
confidence: 99%
“…If the measurements are sensitive to outliers, the 1-norm can be applied in (3) instead of the 2-norm. When prior knowledge of the grid is available, this can be included by adding constraints to the LS problem (3) and making it a convex optimization problem [40] which can be efficiently solved [41].…”
Section: A a Constant Linear Voltage Modelmentioning
confidence: 99%